TYPOLOGY OF FEMINITIVES AND THEIR CULTURAL MARKINGS IN THE RUSSIAN AND UZBEK LANGUAGES: A COMPARATIVE ANALYSIS - Jabborova Nargiza (Modern American Journals, 2025)
The article examines the phenomenon of feminitives — grammatical and lexical units denoting the feminine gender of professions, status and socio-gender roles — in the context of Russian and Uzbek linguistic cultures. The study is aimed at identifying the structural, semantic and stylistic features of feminitives, as well as their socio-cultural marking. On the basis of comparative analysis, the classification of feminitives by the degree of normativity, emotional coloring and perception in society. Literary and journalistic texts, as well as survey data of native speakers of Russian and Uzbek languages were used as empirical material. The results obtained allow us to identify not only the formal differences between the systems, but also to show how cultural and ideological attitudes affect the perception of the female nomination in the language. The article may be useful for specialists in the field of gender linguistics, linguoculturology and language teaching.
Keywords: feminitive, gender nomination, language politeness, cultural marking, Uzbek language, Russian language, linguoculture, stylistics, pragmatics